Україна в польській східній політиці 1989-1999 рр. - Стрільчук, Людмила Василівна; Strilchuk, Liudmyla V. (Волинський національний університет імені Лесі Українки, 2006)
Досліджено польську східну політику щодо України у 1989 – 1999 рр. Проаналізовано чинники, які вплинули на її формування. Вивчено угоди та програми із стратегічного партнерства України та Республіки Польща.

The Polish eastern policy concerning Ukraine in 1989 - 1999 was analyzed. The factors influencing its formation were analyzed. The agreements and programs on strategic partnership between Ukraine and the Republic of Poland were studied.
Ukraine in the Polish Eastern Policy 1989-1999
Keywords: Україна; Республіка Польща; стратегічне партнерство; східна політика; українсько-польські відносини; Ukraine; Republic of Poland; strategic partnership; eastern politics; Ukrainian-Polish relations